Optical Force Sensing with Cylindrical Microcontainers. (7th May 2018) - Meissner, Robert; Oliver, Neus; Denz, Cornelia
Abstract: Quantitative force sensing reveals essential information for the study of biological systems. Forces on molecules, cells, and tissues uncover functioning conditions and pathways. To analyze such forces, spherical particles are trapped and controlled inside an optical tweezers (OT) trap. Although these spherical particles are well‐established sensors in biophysics, elongated probes are envisioned for remote force sensing reducing heat damage caused by OT. There is thus a growing demand for force metrology with OT using complexly shaped objects, e.g., sac‐like organelles or rod‐like bacteria. Here, the employment of Zeolite‐L crystals as cylindrical force sensing probes inside a single optical trap is investigated. It is shown that cylindrical objects can be used as force probes since existing calibration assays can be performed with suitable corrections. Forces of active driving assays are compared with passive calibration methods. Finally, the investigations are extended to direct force measurements based on momentum calibration, in which the influence of rotation due to torque in a single optical trap is unveiled. Simulations reveal the relation between torque and the position of equilibrium in the trap. The results highlight the functionality of Zeolite‐L crystals as probes for force sensing, while opening perspectives for enhanced, accurate force metrology in biophotonics. Abstract : Quantitative force metrology by optical tweezers reveals essential information in biological systems. Current calibration techniques are restricted to the use of spheres as probes, while its application to other potentially advantageous anisotropic objects remains unclear. Investigations combining active calibration assays with direct force measurements show that Zeolite‐L crystals can act as cylindrical force sensors despite the existence of torque.